2020
DOI: 10.1590/s2175-97902019000418371
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro antibacterial activity of essential oils from Murraya paniculata (L.) Jack (Rutaceae) ripe and unripe fruits against bacterial genera Mycobacterium and Streptococcus

Abstract: This study aims to investigate chemical composition of essential oils from Murraya paniculata (L.) Jack (Rutaceae) ripe and unripe fruits and determine their in vitro antibacterial activity. Essential oils were extracted by hydrodistillation from Murraya paniculata (L.) Jack ripe and unripe fruits collected in the Cerrado, in Rio Verde, southwestern Goiás, Brazil. They were analyzed by gas chromatography with flame ionization detector (GC-FID) and by gas chromatography-mass spectrometry (GC-MS). Sesquiterpenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Four-hundred and four volatile oils ( 317 – 711 , Supplementary Table S ) have been isolated from MFC ( Pino et al, 2006 ; Raina et al, 2006 ; Krishnamoorthy et al, 2015 ; Silva et al, 2020 ; Saikia et al, 2021 ). The major volatile organic compounds dominated by benzenoids, sesquiterpenes, diterpenoids, triterpenoids, coumarins, and phenylethanoids in hydrodistillation and pentane, n -hexane, and dichloromethane extracts using GC-MS and gas chromatography-flame ionization detection (GC-FID).…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Four-hundred and four volatile oils ( 317 – 711 , Supplementary Table S ) have been isolated from MFC ( Pino et al, 2006 ; Raina et al, 2006 ; Krishnamoorthy et al, 2015 ; Silva et al, 2020 ; Saikia et al, 2021 ). The major volatile organic compounds dominated by benzenoids, sesquiterpenes, diterpenoids, triterpenoids, coumarins, and phenylethanoids in hydrodistillation and pentane, n -hexane, and dichloromethane extracts using GC-MS and gas chromatography-flame ionization detection (GC-FID).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Most of the volatile oils were sesquiterpene hydrocarbons (80%); the major compound was caryophyllene (20.93%). Silva et al (2020) reported that volatile oils were also effective against Mycobacterium kansasii (MIC 50 = 250 μg/mL) and moderately active against Mycobacterium tuberculosis, demonstrating anti-streptococcal and anti-mycobacterial activities (MIC 50 = 500 μg/mL). GC-FID and GC-MS were used to analyze the volatile oils of M. paniculata leaves using hydrodistillation.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%